Optimality Conditions for Nonconvex Constrained Optimization Problems. (10th December 2019) - Mashkoorzadeh, F.; Movahedian, N.; Nobakhtian, S.
Abstract: We present optimality conditions for a class of nonsmooth and nonconvex constrained optimization problems. To achieve this aim, various well-known constraint qualifications are extended based on the concept of tangential subdifferential and the relations between them are investigated. Moreover, local and global necessary and sufficient optimality conditions are derived in the absence of convexity of the feasible set. In addition to the theoretical results, several examples are provided to illustrate the advantage of our outcomes.